How connected are our conference review boards? - Bhowmick, Sourav S. (2023)
Dense co-authorship network formed by the review board members of a conference may adversely impact the quality and integrity of the review process. In this report, we shed light on the topological characteristics of such networks for three major data management conference venues. Our results show all these venues give rise to dense networks with a large giant component. We advocate to rethink the traditional way review boards are formed to mitigate the emergence of dense networks.